Positive Discipline for Youth - Keith G. Diem; Heidi L. Radunovich; Georgene Bender (EDIS)
Working with youth, especially other people’s, can be a challenge. While some are better behaved than others, they all need acceptance and the opportunity to learn. Especially in groups of mixed ages, experience, or interests, the challenge of a youth leader is to see that disruptive youth do not prevent others from learning or having fun. Their very presence in the group, combined with your wise guidance, will help them learn what is socially acceptable and how to do what is right. This information sheet will help you to understand youth better and to provide some ideas on how to deal with the unruly kids with minimal disruption of the learning situation. This 5-page fact sheet was written by Keith G. Diem, Heidi L. Radunovich, and Georgene Bender, and published by the UF Department of 4-H Youth Development, July 2014.